Fear of an Islamic Planet? Intermedial Exchange and the Rhetoric of Islamophobia - Stefan L. Brandt (European Journal of American Studies)
The post-9/11 era is marked by an unusual rise of Islamophobic rhetoric that permeates the U.S. cultural imaginary and connects a wide range of medial discourses from literature and cinema to television and the World Wide Web. Orientalist stereotypes have informed Hollywood blockbusters and television series as well as acclaimed novels such as Khaled Hosseini’s The Kite Runner (2003), John Updike’s Terrorist (2006), and Mohsin Hamid’s The Reluctant Fundamentalist (2007), not to mention Donald Trump’s speeches and writings on “radical Islamic terrorism.” My essay argues that contemporary public discourse in the U.S. addresses an array of viral images, portraying Muslims as essentially “alien” to mainstream American values. The fears of a potential—or already ongoing—“Islamization of America” are kept alive through continual interaction between texts and images from hegemonic visual discourse, involving what I call “intermedial exchange” between literary texts, films, television shows, magazines, newspapers, and the Internet.